THE PRECEPTS OF INDONESIAN UNITY AS MATERIAL FOR REFLECTION ON IMPLEMENTING HUMAN RIGHTS VALUES - Kevlin Anggriawan (Academic Solution Publisher, 2024)
Indonesia as a state of law and part of the world community, cannot be apathetic about human rights issues. Human Rights is an outward right that is owned by all human beings and comes directly from God Almighty. The ideology of the Indonesian state, namely Pancasila, has determination in upholding human rights. This discussion will focus on the implementation of human rights values ​​in the third principle namely the unity of Indonesia. In writing this article, how the precepts of Indonesian unity can be used as a reference in realizing the values ​​of Human Rights in the life of society, nation and state. Basically, the principle of Indonesian unity is a form of explicit elaboration in implementing human rights in shaping the harmonious life of the Indonesian people through unified and unified actions for the sake of the full peace of life of the Indonesian people. Unity is a means of holistically upholding human rights, because with unity all people will understand their rights and obligations as citizens, especially in upholding human rights.